In-situ bridging of SnO2 nanowires between the electrodes and their NO2 gas sensing characteristics - Kim, Byeong-Guk; Lim, Dong-Gun; Park, Jae-Hwan; Choi, Young-Jin; Park, Jae-Gwan (ELSEVIER, 2011)
A simple and efficient way of making highly sensitive SnO2 nanowire-based gas sensors without an individual lithography process was studied. The SnO2 nanowires network was floated upon the Si substrate by separating the Au catalyst layer from the substrate. As the electric current is transported along the networks of the nanowires, not along the surface layer on the substrate, the gas sensitivities could be maximized in this networked and floated structures. The sensitivity was 5-30 when the NO2 concentration was 1-10 ppm. The response time was ca. 20-60 s. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: CONDUCTION MODEL; OXIDE; SENSITIVITY; SENSORS